2022
DOI: 10.1038/s41467-022-33591-4
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of an ATTRwt amyloid fibril from systemic non-hereditary transthyretin amyloidosis

Abstract: Wild type transthyretin-derived amyloid (ATTRwt) is the major component of non-hereditary transthyretin amyloidosis. Its accumulation in the heart of elderly patients is life threatening. A variety of genetic variants of transthyretin can lead to hereditary transthyretin amyloidosis, which shows different clinical symptoms, like age of onset and pattern of organ involvement. However, in the case of non-hereditary transthyretin amyloidosis ATTRwt fibril deposits are located primarily in heart tissue. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 51 publications
8
35
0
Order By: Relevance
“…These so called "amyloid signature proteins" are common in amyloid deposits in systemic amyloidosis [1] and recently, cryo-EM studies have also revealed a structural polymorphism for protein aggregates associated with systemic amyloidosis. [64][65][66][67][68][69][70] Thus, polymorphic protein aggregates seems to be a common feature for several diseases and fluorescent ligands that can reveal and distinguish polymorphic protein aggregates would be essential for understanding the role of distinct aggregate morphotypes during the pathogenesis of specific diseases, as well as for accurate clinical diagnostics of individual disorders. In this regard, thiophenebased ligands have evolved as a class of fluorescent tools that can be utilized for optical assignment of disease-associated aggregates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These so called "amyloid signature proteins" are common in amyloid deposits in systemic amyloidosis [1] and recently, cryo-EM studies have also revealed a structural polymorphism for protein aggregates associated with systemic amyloidosis. [64][65][66][67][68][69][70] Thus, polymorphic protein aggregates seems to be a common feature for several diseases and fluorescent ligands that can reveal and distinguish polymorphic protein aggregates would be essential for understanding the role of distinct aggregate morphotypes during the pathogenesis of specific diseases, as well as for accurate clinical diagnostics of individual disorders. In this regard, thiophenebased ligands have evolved as a class of fluorescent tools that can be utilized for optical assignment of disease-associated aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Protein aggregates can also contain additional molecules, such as heparan sulphate proteoglycan (HSPG) and serum amyloid P‐component (SAP), [1] that might have an impact on the assembly of the deposits, as well as influence the binding mode of ligands. These so called “amyloid signature proteins” are common in amyloid deposits in systemic amyloidosis [1] and recently, cryo‐EM studies have also revealed a structural polymorphism for protein aggregates associated with systemic amyloidosis [64–70] . Thus, polymorphic protein aggregates seems to be a common feature for several diseases and fluorescent ligands that can reveal and distinguish polymorphic protein aggregates would be essential for understanding the role of distinct aggregate morphotypes during the pathogenesis of specific diseases, as well as for accurate clinical diagnostics of individual disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Next, unfolded TTR monomers assembly into protein oligomers that later propagate into amyloid fibrils (Matsuzaki et al, 2017;Reixach et al, 2004). Steinebrei et al (2022) utilized cryo-electron microscopy (cryo-EM) to resolve the secondary structure of ex vivo extracted TTR fibrils. It was found that TTR fibrils were composed of several monomers that adopted β-sheet secondary structure that propagated in the direction perpendicular to β-strands.…”
Section: Introductionmentioning
confidence: 99%
“…Steinebrei et al (2022) utilized cryo‐electron microscopy (cryo‐EM) to resolve the secondary structure of ex vivo extracted TTR fibrils. It was found that TTR fibrils were composed of several monomers that adopted β‐sheet secondary structure that propagated in the direction perpendicular to β‐strands.…”
Section: Introductionmentioning
confidence: 99%
“…Various precursors proteins are identified as the cause of amyloid formation leading to organ dysfunction, and among those precursors, transthyretin (TTR) protein is known to cause life-threatening organ dysfunction, termed ATTR amyloidosis [ 2 ]. ATTR amyloidosis can be either an age-related amyloid formation from misfolded wild-type TTR (ATTRwt) or by hereditary TTR malfunction due to mutation in the TTR gene (ATTRv) [ 3 ]. Although ATTRwt amyloidosis can cause various diseases, such as cardiac failure, conduction disturbances, arrhythmias and carpal tunnel syndrome, it is still under-recognised, considering its clinical significance with increasing prevalence in the aged population [ 4 ].…”
Section: Introductionmentioning
confidence: 99%